Introduction - Vol 1 - Cooke, Pat; Mark-Fitzgerald, Emily; McCall, Kerry; Durrer, Victoria (Irish Journal of Arts Management and Cultural Policy, 2013)
This article announces and details the rationale and aims for the Irish Journal of Arts Management and Cultural Policy from the perspective of the Editorial Board. We are delighted to launch the Irish Journal of Arts Management and Cultural Policy. As a peer-reviewed, open access e-journal, this platform will publish original research on the arts and cultural sector in Ireland. We hope it will serve as a gathering place for critical thinking and constructive debate on the challenges and opportunities facing arts professionals in Ireland. This inaugural issue is only the start of what we hope will be a shared discussion on a wide spectrum of topics encompassing arts and cultural management; governance; policy decisions/outcomes; cultural economics; arts education; social practices and cultural production. While democratic governments will always need the freedom to respond tactically to circumstances, policy decisions that are concerned with equity, integrity and credibility, must also be rooted in longer-term analysis, critique and a transparent articulation and consideration of principles. As we continue to face new challenges, we hope the Irish Journal of Arts Management and Cultural Policy will serve not only to inform these circumstances but also act as an educational resource for arts management and cultural policy professionals and students.